Marketing factors affecting the making of media products: characteristics and typology - Kornievskaya, Ekaterina D. (Journal of the Belarusian State University. Journalism, 2024)
The article considers marketing factors affecting the making of media products in the editorial offices of mass media. The study identifies eight marketing factors of this order: price, product, place of sale and distribution methods, promotion, volume of sales, product popularity among customers, recognition, as well as reputation in the market. However, the degree of impact varies and depends on several regulatory indicators, including media type, editorial budget (including promotion costs), characteristics of the target audience.
Keywords: mass media; target audience; media products; marketing factors; 4P marketing mix; multimedia release; promotion